Library Instruction in an Interdisciplinary Environmental Studies Program: Challenges, Opportunities, and Reflections - Laurie A. Kutner (Issues in Science and Technology Librarianship)
Teaching library and information skills to students in interdisciplinary areas presents a unique set of challenges for a variety of reasons. Focusing on the experience of delivering multiple, progressive library instruction sessions to undergraduates in the interdisciplinary Environmental Program at the University of Vermont, this article discusses both challenges and opportunities involved in teaching interdisciplinary students library and information skills in the context of our current electronic information environment.